Aspectos matemáticos que amplían la noción de notación científica en el área de física de educación media general - Godoy, Yohan; González, Yusmery (Revista Científica, 2018)
For this work, a constructivist didactic proposal was designed in which the students of the third year of General Media Education can acquire a significant learning in the use of Scientific Notation. The type of research used is among feasible projects with a non-experimental field design. For data collection, the survey technique was used, which was applied to 43 students of the Physics subject of the third year of the Liceo Rosario Almarza Trujillo-Venezuela. The analysis of the results indicated that they present deficiencies in terms of significant numbers and order magnitude, which are essential mathematical aspects for the understanding and use of Scientific Notation in the area of Physics, as well as highlighting the need for Implement other teaching and learning strategies, such as a series of complementary activities for the teacher in the classroom or the student. In view of these results, a didactic guide was carried out using the known mathematical aspects and various ludic activities to extend the notion and use of scientific notation.